2011
DOI: 10.1088/0004-637x/739/2/94
|View full text |Cite
|
Sign up to set email alerts
|

The 2009 Outburst of Magnetar 1e 1547--5408: Persistent Radiative and Burst Properties

Abstract: The magnetar 1E 1547−5408 recently exhibited two periods of outburst, beginning on 2008 October 3 and 2009 January 22. Here we present an analysis of the persistent radiative evolution and a statistical study of the burst properties during the 2009 outburst using the Swift X-ray Telescope (XRT). We find that the 1-10 keV flux increased by a factor of ∼ 500 and hardened significantly, peaking ∼ 6 hours after the onset of the outburst. The observed pulsed fraction exhibited an anticorrelation with phase-averaged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
91
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 49 publications
17
91
3
Order By: Relevance
“…Our mean T 90 values for SGR J1550−5418 are larger than those found for INTEGRAL (68 ms; Savchenko et al 2010), but smaller than the Swift bursts (305 ms; Scholz & Kaspi 2011). This is due to the different sensitivities and energy ranges of the instruments (see also Scholz & Kaspi 2011). Regarding the rise times, we confirm what has been established for other magnetar bursts (e.g., Göǧüş et al 2001;Scholz & Kaspi 2011): the asymmetric T rise /T 90 distributions for single-peaked events indicate that magnetar bursts have shorter rise than decay times, and the bimodal distribution of multiplepeaked events shows that for most bursts the first peak is the brightest.…”
Section: Temporal Analysiscontrasting
confidence: 74%
See 2 more Smart Citations
“…Our mean T 90 values for SGR J1550−5418 are larger than those found for INTEGRAL (68 ms; Savchenko et al 2010), but smaller than the Swift bursts (305 ms; Scholz & Kaspi 2011). This is due to the different sensitivities and energy ranges of the instruments (see also Scholz & Kaspi 2011). Regarding the rise times, we confirm what has been established for other magnetar bursts (e.g., Göǧüş et al 2001;Scholz & Kaspi 2011): the asymmetric T rise /T 90 distributions for single-peaked events indicate that magnetar bursts have shorter rise than decay times, and the bimodal distribution of multiplepeaked events shows that for most bursts the first peak is the brightest.…”
Section: Temporal Analysiscontrasting
confidence: 74%
“…Although the persistent emission energy release cannot be directly measured by GBM or SPI-ACS, Bernardini et al (2011) have shown that for that same time period, it can be at most a factor of five higher in the 13-200 keV than in the 1-10 keV range. The energy released in bursts during a week is thus comparable to the energy released in the persistent emission during an eightmonth period (Scholz & Kaspi 2011), and we conclude that SGR J1550−5418 exhibits similar energetics behavior as other SGR sources .…”
Section: Burst Energeticssupporting
confidence: 53%
See 1 more Smart Citation
“…4a) showed that the ionosphere was remarkably smooth on 22 January 2009 at 01:21 UT. Both BAT and INTEGRAL were triggered with the emission of hundreds of bursts in the band (25 keV-2 MeV) from the source SGR 1550-5418 at 01:32:41 and 02:46 UT, respectively (see Scholz and Kaspi, 2011;Mereghetti et al, 2009). Nearly 10 s after INTEGRAL was triggered, the CIDR started to detect small-scale ionospheric disturbances over the eastern Mediterranean between 30.5 and 41 • geographic latitude at 02:56 UT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The peak of the persistent emission occurred ∼ 6 h after BAT was first triggered. This was accompanied by a hardening of the spectrum in the 1 × 10 keV band (see a summary of the observations in Table 1 in Scholz and Kaspi, 2011). The wide-band allsky monitor (WAM) onboard the Suzaku satellite detected at least 254 bursts in the 0.16-6.2 MeV band over the period of 22 January 2009 00:57-17:02 UT from the direction of the source.…”
Section: Introductionmentioning
confidence: 99%